Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres